Shielding antistatic ton bag lining bag and preparation method thereof
By using modified carbon nanotubes and polyimide nanofibers in the antistatic layer of the bag lined in the ton bag, a conductive network and structural support is formed, the problem of degradation of antistatic performance under temperature changes is solved, and the stable performance of antistatic performance and application stability is achieved.
Patent Information
- Application Number
- CN202411958368.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the environment of severe temperature changes, the molecular migration and diffusion of antistatic agents are affected, resulting in a decrease in antistatic properties and insufficient application stability.
A multi-layer composite film with a structure of PET/antistatic layer/PA/PE is adopted. The antistatic layer is composed of resin material, filler, color masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube. The modified carbon nanotube is obtained by grafting polyaniline. The polyimide nanofiber and modified carbon nanotube form a conductive network, and the antistatic properties are exerted with antistatic agents, and the antistatic agent is protected through the structural stability and thermal conductivity of the polyimide nanofiber.
Under the environment of drastic temperature changes, the excellent and stable performance of antistatic properties is maintained, which improves the application stability and overall quality of the bag lined bags.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ton bag lining materials, and more specifically, to a shielding antistatic ton bag lining bag and a preparation method thereof. Background Art
[0002] Ton bags are a kind of flexible transport packaging container, which is moisture-proof, dust-proof, radiation-resistant, firm and safe, and has sufficient structural strength. As container bags are easy to load and unload, and handling is very convenient, the loading and unloading efficiency is significantly improved, and they have developed rapidly in recent years. Ton bags are usually equipped with liner bags, which can make the ton bags have better load-bearing capacity, thereby ensuring the safety of goods during transportation or stacking, and protecting the goods from pollution and damage from the external environment.
[0003] The structure of the inner liner of a ton bag is usually made of multi-layer co-extruded materials. Common materials for the inner liner of a ton bag include multi-layer composite materials such as PET / Al / PA / PE, PA / Al / PE, PET / Al / PE and PET / PA / PE. These materials combine the advantages of different materials through a composite process, and are soft to the touch and low in cost, making the inner liner widely applicable. Because the inner liner of a ton bag has static electricity, it will adsorb powder materials during the production process, reducing the quality of the inner liner of the ton bag, so it is achieved by adding antistatic agents. At present, the antistatic function is achieved by two methods: internal addition and external coating of antistatic agents; the method of internal addition of antistatic agents adds antistatic components to the inner liner bag, and the method of external coating of antistatic agents is to coat the outer layer of the inner liner bag with antistatic agents.
[0004] Regarding the above-mentioned related technologies, the inventors believe that the ton bag liner bags will be affected by drastic temperature changes during the application process. The drastic temperature changes will affect the migration and diffusion of the antistatic agent molecules and may cause the molecular structure of the antistatic agent to change, thereby causing a significant loss in the antistatic performance of the ton bag liner bags. The overall application stability still needs to be improved.
[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0006] In order to ensure that the antistatic performance of a ton bag liner bag can maintain excellent and stable performance under the influence of an environment with drastic temperature changes, the present application provides a shielded antistatic ton bag liner bag and a preparation method thereof.
[0007] In the first aspect, the present application provides a shielded antistatic ton bag liner bag, which adopts the following technical solution: A shielding antistatic ton bag liner bag is made by processing a multi-layer composite film with a structure of PET / antistatic layer / PA / PE, and the antistatic layer is made of raw materials containing the following parts by weight: Resin material 40-75 parts; 20-40 parts of filler; Masterbatch 5-10 parts; 1-3 parts of antistatic agent; Dispersant 2-5 parts; Antioxidant 0.2-0.4 parts; 4-6 parts of polyimide nanofibers; 1-3 parts of modified carbon nanotubes; The modified carbon nanotubes are prepared by the following method: S1, placing the carbon nanotube raw material in a concentrated nitric acid solution, ultrasonically dispersing it, and then subjecting it to high-temperature reflux, suction filtration and drying to obtain pretreated carbon nanotubes; S2. Dispersing the pretreated carbon nanotubes obtained in step S1 in xylene, and then adding deionized water and p-toluenesulfonic acid to obtain a microemulsion; then adding aniline monomer to the microemulsion under ice bath conditions, mixing evenly, and then adding ammonium persulfate to react. After the reaction is completed, filtering, washing, and drying to obtain modified carbon nanotubes.
[0008] By adopting the above technical solution, the modified carbon nanotubes are obtained by grafting polyaniline onto the surface of the acidified carbon nanotubes, which can show excellent compatibility and dispersibility in the antistatic layer and show better interface bonding with the resin material. At the same time, the modified carbon nanotubes can cooperate with the antistatic agent to exert excellent antistatic performance by forming a conductive network, and use their own excellent structural stability and thermal conductivity under temperature change environment to play a thermal coordination protection role for the antistatic agent, thereby bringing about excellent and stable antistatic performance; and the polyimide nanofibers have excellent performance in temperature change resistance, can maintain their mechanical properties within an extreme temperature range, and can inhibit changes in the molecular structure of the antistatic agent. Furthermore, under the influence of an environment with drastic temperature changes, the stability of the antistatic performance can be improved to a certain extent; at the same time, the polyimide nanofibers and the modified carbon nanotubes can also play an excellent compounding and synergistic role with each other. The polyimide nanofibers are entangled with the modified carbon nanotubes to bring structural support and attachment protection, so that the carbon nanotubes form a conductive network to play an excellent antistatic effect and thermal coordination effect, and it is not easy to cause damage to other raw material mixed matrices in the antistatic layer, so that the antistatic layer can play an excellent antistatic performance. Furthermore, under the influence of an environment with drastic temperature changes, the antistatic performance of the shielding antistatic ton bag liner bag can maintain excellent and stable performance, and the overall application effect is significantly improved.
[0009] Preferably, in the operation of step S2, the weight ratio of the pretreated carbon nanotubes to the aniline monomer is 1:(4-6).
[0010] By adopting the above technical scheme, when the pretreated carbon nanotubes and aniline in the above weight ratio react in step S2, polyaniline can be grafted onto the surface of the carbon nanotubes more evenly, so that the modified carbon nanotubes can form a stronger conductive network when used, and their own stability and thermal coordination protection under the influence of a drastic temperature change environment are also stronger, thereby enabling the antistatic layer to play its role more stably, which is conducive to obtaining a shielding antistatic ton bag liner bag with better application stability.
[0011] Preferably, the weight ratio of the polyimide nanofibers to the modified carbon nanotubes is 5:3.
[0012] By adopting the above technical scheme, when the polyimide nanofibers and modified carbon nanotubes in the above weight ratio are used in combination, the composite effect between them is relatively excellent, so that the antistatic layer can exert excellent and stable antistatic performance under the influence of the environment of drastic temperature changes, and the application quality of the shielded antistatic ton bag liner bag is also better.
[0013] Preferably, the diameter of the polyimide nanofiber is 30-80 nm, and the length is 6-10 μm; the diameter of the carbon nanotube raw material is 10-15 nm, and the length is 1-2 μm.
[0014] By adopting the above technical scheme, when the above heavy-specification polyimide nanofibers and modified carbon nanotubes are used in combination, the composite effect between them is relatively excellent. Whether it is the conductive network formed between the modified carbon nanotubes or the entanglement between the polyimide nanofibers and the modified carbon nanotubes, they are distributed relatively evenly and interact relatively completely, so that the antistatic stability of the antistatic layer under the influence of an environment with drastic temperature changes is also relatively excellent, and a shielding antistatic ton bag liner bag with better application stability can be obtained.
[0015] Preferably, 2-5 parts by weight of porous alumina are added to the raw materials of the antistatic layer.
[0016] By adopting the above technical scheme, the porous alumina has excellent thermal conductivity, and based on its own porous characteristics, when used in the antistatic layer, the polyimide nanofibers and modified carbon nanotubes can partially enter the porous structure of the porous alumina and form a network structure with the porous alumina as the connecting nodes, thereby bringing about a significant improvement in stability and thermal coordination protection, avoiding a large thermal difference inside the antistatic layer under the influence of an environment with drastic temperature changes, thereby significantly improving the stability of the antistatic layer during the application process, and improving the overall application quality of the shielding antistatic ton bag liner.
[0017] Preferably, the porous alumina has a particle size of 300-500 nm, an average pore size of 100-200 nm, and a porosity of 30-50%.
[0018] By adopting the above technical scheme, the porous alumina of the above specifications, when used, has a relatively excellent corresponding effect in combination with polyimide nanofibers and modified carbon nanotubes, and has a more significant effect on improving the stability of the antistatic layer under the influence of an environment with drastic temperature changes. The application quality of the final shielded antistatic ton bag liner bag is also better.
[0019] Preferably, the dispersant is one or a combination of several of stearamide, hexenyl bis stearamide, stearic acid monoglyceride, tristearic acid glyceride, microcrystalline wax, barium stearate, zinc stearate, calcium stearate, ethylene-acrylic acid copolymer and ethylene-vinyl acetate copolymer.
[0020] By adopting the above technical scheme, the dispersant can ensure that the raw materials of each component are fully dispersed and combined to avoid agglomeration, and can improve the processing performance of the antistatic layer so that the raw materials used can exert excellent effects; and the above types of dispersants are all suitable for the preparation of the antistatic layer and can exert the above excellent effects.
[0021] Preferably, the antioxidant is one or a combination of di-tert-butylphenol, triphenyl phosphate, o-phenylenediamine and catechol.
[0022] By adopting the above technical scheme, the antioxidant can effectively inhibit or reduce the thermal oxidation reaction rate of the resin macromolecules, delay the thermal and oxygen degradation process of the resin, thereby significantly improving the heat resistance of the resin, which helps to maintain the stability of the antistatic layer in an environment with drastic temperature changes; and the above types of antioxidants are all suitable for the preparation of the antistatic layer and can exert the above-mentioned excellent effects.
[0023] In the second aspect, the present application provides a method for preparing a shielded antistatic ton bag liner bag, using the following technical solution: A method for preparing a shielding antistatic ton bag liner bag, comprising the following steps: (1) preparing raw materials including resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube according to a proportion; (2) mixing the resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube in step (1) uniformly, and extruding and granulating to obtain an antistatic layer material; (3) The antistatic layer material obtained in step (2) is subjected to four-layer co-extrusion blow molding with PET, PA and PE to obtain a multilayer composite film with a structure of PET / antistatic layer / PA / PE, and then subjected to bag making processing to obtain a shielding antistatic ton bag liner bag.
[0024] By adopting the above technical scheme, the above preparation method is simple to operate. In the preparation process of the antistatic layer material, the raw materials are processed in one pot, which can ensure that the interaction between the raw materials can be excellent. The overall performance is better applicability, and finally the shielding antistatic ton bag liner bag with excellent and stable quality can be obtained, and the whole is also suitable for large-scale industrial production.
[0025] In summary, this application has the following beneficial effects: 1. The present application uses polyimide nanofibers and modified carbon nanotubes in the antistatic layer, and through the compounding and synergistic effect between the two, it can play an excellent thermal coordination and electrostatic protection role, so that the antistatic layer can play an excellent antistatic performance, and then under the influence of the environment of drastic temperature changes, the antistatic performance of the shielding antistatic ton bag liner bag can maintain excellent and stable performance, and the overall application effect is significantly improved; 2. This application uses porous alumina and utilizes the excellent matching effect between porous alumina and polyimide nanofibers and modified carbon nanotubes to bring about a synergistic enhancement effect, so that the stability of the antistatic layer during the application process can be significantly improved, and the overall application quality of the shielding antistatic ton bag liner bag is improved. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0027] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: Metallocene linear polyolefin resin was purchased from MVLDPE (metallocene) Japan Prime SP0540; Low-density polyethylene resin was purchased from Qatar Petrochemical LA0710; The color masterbatch was purchased from the black masterbatch of Jinan Dahua Plastic Processing Plant; The antistatic agent was purchased from Croda Antistatic Agent 129V in the UK.
[0028] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified carbon nanotube is prepared by the following method: S1, taking carbon nanotube raw materials and placing them in concentrated nitric acid solution with a material-liquid ratio of 1g:20mL, after ultrasonic dispersion for 30min, reflux at high temperature of 110°C for 1h, and filter and dry to obtain pretreated carbon nanotubes; S2. Dispersing the pretreated carbon nanotubes obtained in step S1 in xylene, and then adding deionized water and p-toluenesulfonic acid, wherein the weight ratio of the pretreated carbon nanotubes, xylene, deionized water and p-toluenesulfonic acid is 0.1:20:60:2, to obtain a microemulsion; then adding aniline monomer to the microemulsion under ice bath conditions, mixing evenly, and then adding ammonium persulfate solution with a mass fraction of 0.03 g / mL to react, wherein the mixing ratio of the aniline monomer to the ammonium persulfate solution is 1 g:80 mL. After the reaction is completed, filtering, washing and drying are performed to obtain modified carbon nanotubes.
[0029] Note: In the operation of step S2, the weight ratio of the pretreated carbon nanotubes to the aniline monomer is 1:5; the diameter of the carbon nanotube raw material is 12.5 nm and the length is 1.5 μm.
[0030] Preparation Example 2 A modified carbon nanotube is different from the preparation example 1 in that, in the operation of step S2, the weight ratio of the pretreated carbon nanotube to the aniline monomer is 1:4.
[0031] Preparation Example 3 A modified carbon nanotube, which is different from Preparation Example 1 in that, in the operation of step S2, the weight ratio of the pretreated carbon nanotube to the aniline monomer is 1:6.
[0032] Preparation Example 4 A modified carbon nanotube, which is different from the one in Preparation Example 1 in that the diameter of the carbon nanotube raw material is 10 nm and the length is 1 μm.
[0033] Preparation Example 5 A modified carbon nanotube, which is different from the one in Preparation Example 1 in that the diameter of the carbon nanotube raw material is 15 nm and the length is 2 μm. Example
[0034] Example 1 A shielding antistatic ton bag liner is prepared by processing a multilayer composite film having a structure of PET / antistatic layer / PA / PE. The raw materials used to prepare the antistatic layer and their corresponding weights are shown in Table 1. The shielding antistatic ton bag liner is prepared by the following steps: (1) preparing raw materials including resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube according to a proportion; (2) mixing the resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube in step (1) uniformly, and extruding and granulating to obtain an antistatic layer material; (3) The antistatic layer material obtained in step (2) is subjected to four-layer co-extrusion blow molding with PET, PA and PE to obtain a multilayer composite film with a structure of PET / antistatic layer / PA / PE, and then subjected to bag making processing to obtain a shielding antistatic ton bag liner bag.
[0035] Note: In the above operation, the resin material is composed of metallocene linear polyolefin resin and low-density polyethylene resin in a weight ratio of 3:2; the filler is talcum powder; the dispersant is stearamide; the antioxidant is di-tert-butylphenol; the diameter of the polyimide nanofiber is 55nm and the length is 8μm; the modified carbon nanotubes are obtained in Preparation Example 1.
[0036] Example 2-3 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the raw materials used to prepare the antistatic layer and their corresponding weights are shown in Table 1.
[0037] Table 1 Raw materials used for preparing the antistatic layer in Examples 1-3 and their weight portions (kg / portion) raw material Example 1 Example 2 Example 3 Resin 57.5 40 75 filler 30 20 40 Masterbatch 7.5 5 10 Antistatic Agents 2 1 3 Dispersants 3.5 2 5 Antioxidants 0.3 0.2 0.4 Polyimide Nanofibers 5 4 6 Modified carbon nanotubes 2 1 3 Example 4 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the diameter of the polyimide nanofiber is 30 nm and the length is 6 μm.
[0038] Example 5 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the diameter of the polyimide nanofiber is 80 nm and the length is 10 μm.
[0039] Example 6 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the modified carbon nanotubes are obtained in Preparation Example 2.
[0040] Example 7 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the modified carbon nanotubes are obtained in Preparation Example 3.
[0041] Example 8 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the modified carbon nanotubes are obtained in Preparation Example 4.
[0042] Example 9 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the modified carbon nanotubes are obtained in Preparation Example 5.
[0043] Example 10 A shielding antistatic ton bag liner bag, which is different from Example 1 in that 3.5 parts by weight of porous alumina are also added to the raw materials of the antistatic layer, and the porous alumina is added together with other raw materials in the operation of step (2); wherein the particle size of the porous alumina is 400nm, the average pore size is 150nm, and the porosity is 40%.
[0044] Embodiment 11 A shielding antistatic ton bag liner bag, which is different from Example 10 in that the weight portion of porous alumina added is 2 parts.
[0045] Example 12 A shielding antistatic ton bag liner bag, which is different from Example 10 in that the weight portion of porous alumina added is 5 parts.
[0046] Example 13 A shielding antistatic ton bag liner bag, which is different from Example 10 in that the particle size of the porous alumina is 300nm, the average pore size is 100nm, and the porosity is 30%.
[0047] Embodiment 14 A shielding antistatic ton bag liner bag, which is different from Example 10 in that the particle size of the porous alumina is 500nm, the average pore size is 200nm, and the porosity is 50%.
[0048] Embodiment 15 A shielding antistatic ton bag liner bag is different from Example 1 in that the total amount of polyimide nanofibers and modified carbon nanotubes remains unchanged, and the weight ratio of the two is adjusted to 5:3.
[0049] Comparative Example Comparative Example 1 A shielding antistatic ton bag liner bag is different from Example 1 in that polyimide nanofibers are not used in the raw materials of the antistatic layer.
[0050] Comparative Example 2 A shielding antistatic ton bag liner bag, which is different from Example 1 in that modified carbon nanotubes are not used in the raw materials of the antistatic layer.
[0051] Comparative Example 3 A shielding antistatic ton bag liner bag is different from Example 1 in that polyimide nanofibers and modified carbon nanotubes are not used in the raw materials of the antistatic layer.
[0052] Comparative Example 4 A shielding antistatic ton bag liner bag, which is different from Example 1 in that the modified carbon nanotubes and other materials are replaced by carbon nanotube raw materials.
[0053] Comparative Example 5 A shielded antistatic ton bag liner bag, which is different from comparative example 1 in that modified carbon nanotubes and other materials are replaced by carbon nanotube raw materials.
[0054] Comparative Example 6 A shielding antistatic ton bag liner bag, which is different from Example 10 in that polyimide nanofibers and modified carbon nanotubes are not used in the raw materials of the antistatic layer.
[0055] Performance test samples: The shielding antistatic ton bag liner bags obtained in Examples 1-15 were used as test samples 1-15, and the shielding antistatic ton bag liner bags obtained in Comparative Examples 1-6 were used as control samples 1-6; wherein, the size of the shielding antistatic ton bag liner bags was 1.2m×1.2m×1.5m, and the thickness of each layer of its structure PET / antistatic layer / PA / PE was 15μm, 30μm, 20μm, and 100μm, respectively.
[0056] Test method: For shielded antistatic ton bag liner bags, test according to the method content in GB / T 14447-1993 "Plastic film electrostatic test method half-life method" to obtain the half-life time, recorded as T1; The principle of the charge half-life test is to measure the time required for the surface potential of the film to decay to half of its initial value in an electrostatic field. The shorter the half-life, the faster the static electricity dissipates, indicating that the antistatic performance is better; Then, the shielded ton bag liner is placed in a high and low temperature alternating test chamber, with an initial temperature of 25°C. The temperature is first raised to 80°C at 3°C / min, then lowered to -20°C at 1.5°C / min, and then raised to 25°C at 2°C / min, which is recorded as 1 cycle. After 20 cycles, the half-life time is obtained by testing according to the above method, which is recorded as T2. Finally, the growth rate of the half-life time is calculated, and the growth rate of the half-life time = (T2-T1) / T1; the greater the growth rate of the half-life time, the worse the stability of the shielded antistatic ton bag liner bag under the influence of temperature changes.
[0057] According to the above method, after completing the test samples 1-15 and the control samples 1-6 in turn, the experimental results are recorded in Table 2 accordingly.
[0058] Table 2 Test results of test samples 1-15 and control samples 1-6 sample Half-life time growth rate (%) Test sample 1 3.2 Test sample 2 4.1 Test sample 3 3.8 Test sample 4 4.0 Test sample 5 3.7 Test sample 6 3.9 Test sample 7 3.6 Test sample 8 4.2 Test sample 9 3.5 Test sample 10 1.1 Test sample 11 1.5 Test sample 12 1.4 Test sample 13 1.6 Test sample 14 1.3 Test sample 15 2.8 Control sample 1 10.9 Control sample 2 12.8 Control sample 3 15.6 Control sample 4 8.9 Control sample 5 11.7 Control sample 6 14.2 Combining Examples 1-3 and Comparative Examples 1-3 and Table 2, it can be seen that by using polyimide nanofibers and modified carbon nanotubes in the antistatic layer, the antistatic stability of the shielded antistatic ton bag liner bag can be significantly improved. In the above test, after experiencing drastic stability changes, the growth rate of the half-life time is relatively low, and the performance is relatively excellent; and if any one of the polyimide nanofibers and modified carbon nanotubes is used alone, although it can bring about an improvement in antistatic stability, the improvement is effective but limited, and the sum of the improvement effects brought by the use of each alone is far less than the excellent improvement effect brought by the combination of the two. It can be seen that the combination of polyimide nanofibers and modified carbon nanotubes can play an excellent compound synergistic role. Combined with Comparative Examples 4-5 and Table 2, it can be seen that if the modified carbon nanotubes are replaced with carbon nanotube raw materials, it is found that the growth rate of the half-life time obtained by the test will be significantly increased, and the combination of the carbon nanotube raw materials and the polyimide nanofibers can only bring about a simple superposition of effects, but cannot exert an excellent compound synergistic effect. It can be seen that the use of modified carbon nanotubes can exert a more significant effect with the polyimide nanofibers, thereby improving the antistatic stability of the shielding antistatic ton bag liner bag.
[0059] It can be seen from Example 1 and Example 4-9 and Table 2 that in the preparation of modified carbon nanotubes, the weight ratio of pretreated carbon nanotubes and aniline monomers is controlled to be 1: (4-6), and the diameter of the carbon nanotube raw material is selected to be 10-15nm and the length is 1-2μm. The modified carbon nanotubes finally obtained can all exert excellent and stable effects. At the same time, the diameter of the polyimide nanofiber is 30-80nm and the length is 6-10μm, which can also form an excellent match with the modified carbon nanotubes, so that the antistatic layer can exert excellent and stable antistatic performance under the influence of the environment with drastic temperature changes, and the application quality of the shielded antistatic ton bag liner is finally obtained. Among them, when the weight ratio of polyimide nanofibers and modified carbon nanotubes is 5: 3, it is conducive to obtaining a shielded antistatic ton bag liner with better application stability.
[0060] Combining Example 1 and Examples 10-14 with Table 2, it can be seen that the addition of porous alumina can further improve the antistatic stability of the antistatic layer under the influence of a drastic temperature change environment, and the growth rate of the half-life time obtained by the test is further reduced. Combining Comparative Examples 2 and 6 with Table 2, it can be seen that if the antistatic layer lacks polyimide nanofibers and modified carbon nanotubes, the improvement effect brought by porous alumina will be greatly discounted, indicating that porous alumina has a synergistic effect with polyimide nanofibers and modified carbon nanotubes, which can significantly improve the application stability of the antistatic ton bag liner.
[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A shielded antistatic ton bag liner bag, characterized in that: It is made by processing a multi-layer composite film with a structure of PET / antistatic layer / PA / PE, and the antistatic layer is made of raw materials containing the following parts by weight: Resin material 40-75 parts; 20-40 parts of filler; Masterbatch 5-10 parts; 1-3 parts of antistatic agent; 2-5 parts of dispersant; Antioxidant 0.2-0.4 parts; 4-6 parts of polyimide nanofibers; 1-3 parts of modified carbon nanotubes; The modified carbon nanotubes are prepared by the following method: S1, placing the carbon nanotube raw material in a concentrated nitric acid solution, ultrasonically dispersing it, and then subjecting it to high-temperature reflux, suction filtration and drying to obtain pretreated carbon nanotubes; S2. Dispersing the pretreated carbon nanotubes obtained in step S1 in xylene, and then adding deionized water and p-toluenesulfonic acid to obtain a microemulsion; then adding aniline monomer to the microemulsion under ice bath conditions, mixing evenly, and then adding ammonium persulfate to react. After the reaction is completed, filtering, washing, and drying to obtain modified carbon nanotubes.
2. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: In the operation of step S2, the weight ratio of the pretreated carbon nanotubes to the aniline monomer is 1:(4-6).
3. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: The weight ratio of the polyimide nanofiber to the modified carbon nanotube is 5:
3.
4. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: The diameter of the polyimide nanofiber is 30-80 nm, and the length is 6-10 μm; the diameter of the carbon nanotube raw material is 10-15 nm, and the length is 1-2 μm.
5. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: The raw materials of the antistatic layer are further added with 2-5 parts by weight of porous alumina.
6. The shielding antistatic ton bag liner bag according to claim 5 is characterized by: The porous alumina has a particle size of 300-500 nm, an average pore size of 100-200 nm, and a porosity of 30-50%.
7. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: The dispersant is one or a combination of stearamide, hexenyl bis stearamide, stearic acid monoglyceride, tristearic acid glyceride, microcrystalline wax, barium stearate, zinc stearate, calcium stearate, ethylene-acrylic acid copolymer and ethylene-vinyl acetate copolymer.
8. The shielding antistatic ton bag liner bag according to claim 1 is characterized by: The antioxidant is one or a combination of di-tert-butylphenol, triphenyl phosphate, o-phenylenediamine and catechol.
9. The method for preparing the shielding antistatic ton bag liner bag according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube according to the proportion; (2) the resin material, filler, masterbatch, antistatic agent, dispersant, antioxidant, polyimide nanofiber and modified carbon nanotube in step (1) are mixed evenly, and then extruded and granulated to obtain an antistatic layer material; (3) The antistatic layer material obtained in step (2) is subjected to four-layer co-extrusion blow molding with PET, PA and PE to obtain a multilayer composite film with a structure of PET / antistatic layer / PA / PE, and then subjected to bag making processing to obtain a shielding antistatic ton bag liner bag.
Citation Information
Patent Citations
Anti-static moistureproof shielding bag
CN103010577A
Composite film suitable for producing moisture-proof and anti-static packing bags
CN104999737A
Conductive polyaniline carbon nano-tube core-shell hybrid composite material as well as preparation method and application thereof
CN109384919A
Carbon nanotubes in carrier tape, cover tape and static shielding bags
CN110712857A
Antistatic polyester film
CN117126443A
Cited By
Shielding material composition, shielding material, preparation method of shielding material, shielding material and application of shielding material
CN120271910A
Shielding material composition, shielding material and preparation method thereof, shielding material and application thereof
CN120271910B
Anti-static polyester film and preparation method thereof
CN120716130A